Localization and domain characterization of the SflA regulator of flagellar formation in Vibrio alginolyticus. (22nd May 2017) - Inaba, Satoshi; Nishigaki, Takehiko; Takekawa, Norihiro; Kojima, Seiji; Homma, Michio
Abstract : Many swimming bacteria use flagella as locomotive organelles. The spatial and numerical regulation of flagellar biosynthesis differs by bacterial species. The marine bacteria Vibrio alginolyticus use a single polar flagellum whose number is regulated positively by FlhF and negatively by FlhG. Cells lacking FlhF and FlhG have no flagellum. The motility defect in an flhFG deletion was suppressed by a mutation in the sflA gene that resulted in the production of multiple, peritrichous flagella. SflA is a Vibrio ‐specific protein. SlfA either facilitates flagellum growth at the cell pole or prevents flagellar formation on the cell body by an unknown mechanism. Fluorescent protein fusions to SflA localized to the cell pole in the presence of FlhF and FlhG, but exhibited both polar and lateral cell localization in Δ flhFG cells. Polar localization of SflA required the polar landmark protein HubP. Over‐expression of the C‐terminal region of SflA (SflAC ) in Δ flhFG Δ sflA cells suppressed the lateral flagellar formation. Our results suggest that SflA localizes with the flagella and that SflAC represses the flagellar initiation in Δ flhFG strains. A model is presented where SflA inhibits lateral flagellar formation to facilitate single polar flagellum assembly in V. alginolyticus cells. Abstract : Marine bacterium Vibrio alginolyticus has a single polar flagellum whose number is regulated positively by FlhF and negatively by FlhG. The sflA gene seems to prevent the flagellation to form peritrichous sites. We have shown that the dependence of the polar localization of SflA on HubP, which is a polar landmark protein anchoring various proteins, including FlhG. We presented a model how V. alginolyticus control the spatial and numerical regulation of polar flagella.